TANGGAPAN PENGUNJUNG PADA PRODUK WISATA AEK SIJORNI DI KABUPATEN TAPANULI SELATAN PROVINSI SUMATERA UTARA - Pakpahan, Reo Rinaldy; Yulia, Nur Arini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze visitors' perceptions of the tourism products offered at Aek Sijorni Tourist Attraction and to identify which components are considered the most appealing and dominant by tourists. The research was motivated by the growing number of visitors after the COVID-19 pandemic, which has been accompanied by complaints regarding the quality of facilities, services, and overall visitor experience. A descriptive quantitative method was employed, using purposive sampling with 100 respondents who met specific criteria. Data were collected through field observations, questionnaires, and documentation, then analyzed using descriptive statistical techniques. The findings indicate that, in general, visitors responded positively to the tourism products, particularly in terms of natural attractions. However, some deficiencies were noted in supporting aspects such as amenities and accessibility, including limited parking space and the lack of recreational facilities. The most prominent attraction, as perceived by visitors, is the multi-tiered waterfall with clear water, surrounded by a lush and serene natural environment. Therefore, it is recommended that management enhance infrastructure and service quality to improve visitor satisfaction and ensure a sustainable tourism experience. Keywords: Visitor Perception, Tourism Product, Aek Sijorni, Natural Attraction, Amenities, Accessibility, Service.